Guidelines for Facilitating Stakeholders Roles in Community Engagement in Green Social Infrastructure Development - Masrom, Md Asrul Nasid; Ohueri, Chukwuka Christian; Azman, Ajlaa Najihah; Chan, Melissa (International Journal of Sustainable Construction Engineering and Technology, 2024)
Green social infrastructure development is crucial for fostering environmentally friendly and socially inclusive communities. Stakeholder-community engagement integrates diverse perspectives, local knowledge, and cultural values into green social infrastructure, reflecting the community's identity. However, stakeholders do not adequately engage the community in decision-making processes during the green social infrastructure development, primarily due to the lack of clear and comprehensive guidelines. The aim of this study is to develop guidelines to enable stakeholders to adequately engage with communities during the development of green social infrastructure. An in-depth interview was conducted with 10 construction stakeholders in Malaysia and the data gathered were analyzed using Thematic Content Analysis. The findings reveal that stakeholders' integration with the community, involvement of the community in all project phases, and provision of adequate healthcare services for the communities are among the most effective guidelines that will facilitate stakeholder role in community engagement in the development of green social infrastructure. As a result, recommendations were made for effective stakeholder community engagement such as conducting a socio-economic study in the target area and preparing a petition box for the communities to communicate with stakeholders. The outcome of this research provides insight to stakeholders on their roles in incorporating sustainable practices that aligns with community needs, which in turn foster a sense of ownership, thereby paving the way for a greener and more resilient future in Malaysia.